Perspektif Pelaku Dalam Penyalahgunaan Narkotika Oleh Oknum Petani - Nisa, Khairun; Neri Widya Ramailis (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to understand the perspectives of perpetrators in cases of drug abuse by farmers within the jurisdiction of the Rimba Melintang Police, Rokan Hilir Regency. This study uses a descriptive approach with qualitative methods, and data is obtained through interviews with perpetrators, police officers, and community leaders. The results show that drug abuse by perpetrators is driven by economic pressures, environmental influences, and minimal knowledge about the impact of narcotics. Rational Choice Theory is used to analyze the perpetrators' actions, which are based on rational calculations in decision-making. Perpetrators are aware of the legal and social risks they pose, but still choose to use drugs as a form of escape from the realities of life. The conclusions of this study emphasize the importance of community-based preventive interventions and education in agrarian environments as a strategy to prevent drug abuse. Keywords: Drug Abuse, Farmers, Perpetrator Perspective, Rational Choice Theory